Tomatillo—Physalis ixocarpa Brot. ex Hornem. - James M. Stephens (EDIS)
This document provides an overview of the tomatillo (Physalis ixocarpa), a fruit-bearing plant related to the husk tomato. It discusses the plant’s introduction from Mexico, its limited cultivation in South Florida, and its popularity among Spanish Americans. The document outlines cultivation practices suitable for Florida gardens, highlights susceptibility to tomato fruit worm, and describes the tomatillo’s culinary uses, particularly in Mexican cuisine such as chili sauces. Original publication date May 1994.